Characteristics of Farm Equipment‐Related Crashes Associated With Injury in Children and Adolescents on Farm Equipment. Issue 2 (3rd December 2015) - Toussaint, Maisha; Faust, Kayla; Peek‐Asa, Corinne; Ramirez, Marizen
Abstract: Purpose: Operating or riding on farm equipment is one of the leading causes of farm‐related injuries and fatalities among children and adolescents. The aim of this study is to examine environment, crash, vehicle, and occupant characteristics and the probability of injury, given a crash, in youth under age 18 on farm equipment. Method: Data from the Departments of Transportation on farm equipment‐related crashes across 9 Midwestern states from 2005‐2010 were used. Odds ratios were calculated using logistic regression to assess the relationship between environment, crash, vehicle, and occupant characteristics and the probability of injury, given a crash. Findings: A total of 434 farm equipment‐related crashes involved 505 child or adolescent occupants on farm equipment: 198 passengers and 307 operators. Passengers of farm equipment had 4.1 higher odds of injury than operators. Occupants who used restraints had significantly lower odds of injury than those who did not. Furthermore, occupants on farm equipment that was rear‐ended or sideswiped had significantly lower odds of injury compared to occupants on farm equipment involved in noncollision crashes. Likewise, occupants on farm equipment that was impacted while turning had significantly lower odds of injury compared to those on equipment that was impacted while moving straight. Conclusion: Precautions should be taken to limit or restrict youth from riding on or operating farm equipment. These findings reiterate the need to enforce policies that improve safety measures for youth involved in or exposed to agricultural tasks.